IMPLEMENTASI PROGRAM PEMBANGUNAN JARINGAN IRIGASI DI KABUPATEN SUMEDANG - Agustin, Irma Dewi; Akadun; Apriani, Vina; Abdurohman, Iqbal; Alfadilah, Willy; Mutiasari, Dewi (LPPM UNSAP & FISIP UNSAP, 2024)
This research aims to find out, get objective data and information about the implementation of irrigation network development programs in Pasanggrahan Village of the Sumedang District Office of Public Works and Spatial Planning. The methods used in this study are qualitative research methods with data collection, observation steps, in-depth interviews and documentation. From this research obtained obstacles regarding the implementation of irrigation network development program in Pasanggrahan Village, Public Works Office and Spatial Arrangement of Sumedang Regency, namely lack of support from the community for irrigation development, poor geographical conditions, lack of support from various parties to the construction of irrigation networks. Efforts to overcome obstacles include increasing socialization to the community about the construction of irrigation networks, making observations to the field first, socializing to the parties concerned around the Sumedang Regency.